Конвенция о правах инвалидов - United Nations (United Nations, 2014)
The Training Guide is for facilitators of training courses on the Convention on the Rights of Persons with Disabilities and its Optional Protocol who are already familiar with the international human rights system. The Convention challenges customs and behaviour based on stereotypes, prejudices, harmful practices and stigma relating to persons with disabilities, and promotes their full participation in all spheres of life. It is already applicable in 137 countries around the world. The Training Guide’s methodology is interactive and promotes a participatory approach. Its modules can be used to develop tailored training courses to meet the needs of specific audiences (government officials, health professionals, civil society, employers’ organizations, etc.). It is also helpful as a general information resource on the Convention and its Optional Protocol.